2020
DOI: 10.1002/ldr.3596
|View full text |Cite
|
Sign up to set email alerts
|

Rotational grazing promotes grassland aboveground plant biomass and its temporal stability under changing weather conditions on the Qinghai‐Tibetan plateau

Abstract: The aboveground biomass (AGB) production of grazed grasslands is mediated by climate, soil nutrients, livestock and other factors. How the biotic and abiotic factors directly or indirectly regulate AGB remains unclear. To fill this gap, from 2014 to 2017, we conducted a rotational grazing experiment to examine the response of AGB to biotic and abiotic factors in Nagqu, a typical alpine meadow community on the Qinghai-Tibetan Plateau. Six yaks were rotationally grazed among three plots from July to September, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Previous studies have indicated that perturbations affected community stability via several mechanisms, namely, species diversity, compensatory dynamics, mean-variance scaling and species dominance [6,53]. In our study, a positive relationship between species richness and community stability was noted.…”
Section: Effects Of Fertilization and Grazing On The Underlying Mechasupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have indicated that perturbations affected community stability via several mechanisms, namely, species diversity, compensatory dynamics, mean-variance scaling and species dominance [6,53]. In our study, a positive relationship between species richness and community stability was noted.…”
Section: Effects Of Fertilization and Grazing On The Underlying Mechasupporting
confidence: 70%
“…However, Beck et al [52] found that moderate grazing promoted the community stability in California's largest serpentine grassland via limiting the infestation of exotic weeds and maintaining native plant communities. Also, Li et al [53] found that rotational grazing increased community stability as grazing improved community productivity and maintained the compensatory growth of the plants on the Qinghai Tibetan plateau ecosystem [53]. The differential responses of community stability to grazing recorded between our study and those by the Beck et al [52] and Li et al [53] could be due to differential grazing methods, climate regions, and vegetation types [49,52].…”
Section: Effects Of Fertilization and Grazing On Community Stabilitymentioning
confidence: 46%
“…Previous studies have examined the responses of temporal stability of plant community biomass to external perturbations such as climate warming (Ma et al, 2017), grazing (Li et al, 2020) and nitrogen deposition (Zhou et al, 2020). Second, while most previous studies on the temporal stability of plant community biomass of grasslands were examined only during the peak plant growth stage, our study covered the full plant growth period from the pre-growth to peak-growth stage, which can better reveal the stability of grassland community dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, plant compensatory growth under livestock grazing was observed in the Eurasian steppe ecosystems that are dominated by C 3 grasses when the growing season was wet (Schönbach et al 2011). In alpine and subalpine regions where are cold and wet, such as the QTP where alpine meadow ecosystems occupy over 4.5 × 10 5 km 2 of the area (Miehe 2008), both clipping (Klein, Harte, and Zhao 2007) and livestock grazing (Zhu et al 2010;Li et al 2020a) caused plant compensatory growth. A meta-analysis suggests that plant compensatory growth, which is a primary mechanism that causes the enhancement of belowground biomass, is generally detected under moderate grazing intensity on the QTP (Sun et al 2019).…”
Section: Compensatory Growth Phenomenamentioning
confidence: 99%